2009
DOI: 10.3354/ab00187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrient supply on photosynthesis and pigmentation in Ulva lactuca (Chlorophyta): responses to short-term stress

Abstract: The effects of nutrient supply on photosynthesis (estimated as chlorophyll fluorescence), chlorophyll content, biomass yield and proximate chemical composition of tank cultivated Ulva lactuca L. (Chlorophyta) were evaluated. To assess the effect of nutrient supply on resistance capacity against short-term stress, algae grown in high nutrient supply (HNS) fishpond effluents and in low nutrient supply (LNS) oligotrophic seawater were transferred to small vessels with increased irradiance of PAR and UV radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 53 publications
(65 reference statements)
5
19
0
Order By: Relevance
“…The greater activation of photoprotective mechanisms in U. lactuca than in S. vulgare, followed by H. spinella, also indicates that dynamic photoinhibition and other expected mechanisms such as production of UV screening and antioxidant substances could also be related to the depth zonation (light history) of the species. In addition, although the HNS cultured U. lactuca is a shade-grown algae (Figueroa et al 2009), it exhibited a very high capacity for acclimation to high irradiance (high recovery) and the highest photosynthetic capacity (ETR). This could be largely due to the positive effect of nutrient supply on photoprotection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The greater activation of photoprotective mechanisms in U. lactuca than in S. vulgare, followed by H. spinella, also indicates that dynamic photoinhibition and other expected mechanisms such as production of UV screening and antioxidant substances could also be related to the depth zonation (light history) of the species. In addition, although the HNS cultured U. lactuca is a shade-grown algae (Figueroa et al 2009), it exhibited a very high capacity for acclimation to high irradiance (high recovery) and the highest photosynthetic capacity (ETR). This could be largely due to the positive effect of nutrient supply on photoprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Ulva lactuca was also cultured in ambient, low nutrient supply (LNS) seawater or in high nutrient supply (HNS) seawater with fishpond effluents at the National Center for Mariculture (Israel Oceanographic & Limnological Research). Growth conditions of U. lactuca in the aquaculture system are reported in Figueroa et al (2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study on nutrient uptake characteristics of algae with different life strategies suggested that ni trogen uptake characteristics were aligned to growth strategies and the adaptation of individual species to local nitrogen supply regimes (short-term pulses vs. long-term exposure) (Martínez et al 2012). Figueroa et al (2009) demonstrated the effect of nutrient regime on the capability of Ulva lactuca to respond to temperature and light stress; how such short-term responses are influenced by additional im pacts of high-CO 2 levels is not certain. On the shores of southern Spain, Ulva rigida C. Agardh, Ellisolandia elongata (J. Ellis & Solander) K. R. Hind & G. W. Saunders (formerly Corallina elongata) and Cystoseira tamariscifolia (Hudson) Papenfuss inhabit exposed rocky mid-to low-intertidal shores in close vicinity (Figueroa et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, De Valera (1940) claims that this phenomena is caused by high concentrations of nutrients in marine water, therefore the change in pigmentation can be used as a contamination indicator. The last experimental ex situ examinations (Figueroa et al 2009;Villares and Carballeira 2004) conducted on marine species of Ulva (U. intestinalis, U. rigida, U. lactuca) also confirmed that nutrient availability has an influence on the pigmentation of thalli and their photosyntheses ratio. Han et al (2008) point out that high concentrations of heavy metals (e.g.…”
Section: Competitionmentioning
confidence: 80%